A drop in Sahara dust fluxes records the northern limits of the African Humid Period - Daniel Palchan; Adi Torfstein (Nature Communications, 2019)
Marine sediment cores from east of Africa show that Sahara dust fluxes decreased by at least 50% between the last deglaciation and the mid Holocene, while the Northern Sector of the Red Sea remained unchanged. This constrains the African Humid Period impact to have extended up to ca. 22°N, across a more limited region than previously thought.